2018
DOI: 10.1177/1591019918754380
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic impingement and the initiation of intracranial side-wall aneurysms

Abstract: Objective The natural history intracranial aneurysms (IA) remains poorly understood despite significant morbidity and mortality associated with IA rupture. Hemodynamic impingement resulting in elevations in wall shear stress and wall shear stress gradient (WSSG) has been shown to induce aneurysmal remodeling at arterial bifurcations. We investigate the hemodynamic environment specific to side-wall pre-aneurysmal vasculature. We hypothesize that fluid impingement and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…197 Blood flow in IA exhibits several fluid dynamics phenomena depending on the morphology of parent and daughter arteries, as well as the size and location of the IA. Shear layers, 198 precessing vortices, 199,200 jet impingement, 201,202 recirculation and separation zones 203,204 are inherently found in IAs. IA hemodynamics, therefore, are quite different from pulsatile pipe flows investigated in literature for turbulence transition criteria.…”
Section: Resultsmentioning
confidence: 99%
“…197 Blood flow in IA exhibits several fluid dynamics phenomena depending on the morphology of parent and daughter arteries, as well as the size and location of the IA. Shear layers, 198 precessing vortices, 199,200 jet impingement, 201,202 recirculation and separation zones 203,204 are inherently found in IAs. IA hemodynamics, therefore, are quite different from pulsatile pipe flows investigated in literature for turbulence transition criteria.…”
Section: Resultsmentioning
confidence: 99%
“…32 Riccardello et al also concluded that secondary flow patterns may play a major role in the initiation of side-wall aneurysm initiation. 33…”
Section: Reason For Observation Of High Wssd and High Plc In Bifurcation And Sidewall De Novo Casesmentioning
confidence: 99%
“…[18][19][20][21][22] More recently, location-based hemodynamic and computed fluid dynamic models have been conducted to understand the appearance and evolution of IA and have demonstrated different patterns of WSS in the cerebral arterial tree. [23][24][25][26] Considering the importance of WSS sensing in aneurysmal disease, we hypothesized that IAs distribution and the diameter of affected arteries could differ between ADPKD and non-ADPKD patients. To investigate differences between demographic data of ADPKD and non-ADPKD patients and differences between characteristics of their IAs, we analyzed combined data from six studies from the literature and three independent cohorts.…”
Section: Introductionmentioning
confidence: 99%